Effect of Exercise on Behavioral Symptoms and Pain in Patients With Dementia Living in Nursing Homes. Issue 2 (March 2019) - Maltais, Mathieu; Rolland, Yves; Vellas, Bruno; Haÿ, Paul-Emile; Armaingaud, Didier; Cestac, Philippe; Rouch, Laure; Cesari, Matteo; de Souto Barreto, Philipe
Objectives: Examine the effects of a 6-month exercise intervention on neuropsychiatric symptoms, pain, and medication consumption in older people with dementia (PWD) living in nursing homes (NH). Methods: Ninety-one older PWD living in NH performed a 6-month structured exercise intervention (n = 44) or a social activity intervention (n = 47). Neuropsychiatric symptoms were measured by the neuropsychiatric inventory (NPI), pain was assessed using the Algoplus scale, and dementia-related drug prescriptions were obtained for all participants. Results: Between-group analysis found a nonsignificant difference that could be of clinical relevance: a 4-point difference in the NPI and 1.3-point difference in the reduction of the number of medications favoring exercisers. No significant differences were found for pain, and a trend was found for an increase in medication consumption in the social group. Conclusion: Exercise effects did not differ from social intervention effects on neuropsychiatric symptoms, pain, and medication consumption in older PWD living in NH.